PSIKOLOGI Psikologi Pendidikan Terkait Dengan Proses Perkembangan Dan Hubungan Dengan Proses Belajar - Rahmah Ninda; Marhamah Marhamah (FKIP Universitas Palangka Raya, 2023)
Basically the problem of pedagogic psychology is the business of students, because education is the treatment of students, who must respond psychologically to the living conditions of students. Thus, psychological problems in children's education can be answered when educators with the help of guidance can help students to develop naturally. Educational psychology is a science that studies human behavior in the concept of learning and teaching and has a close relationship with teaching. The purpose of this research is to describe the stages of development and the relationship between these stages in learning. It denotes changes in human development and the effect they have on the tasks one performs.